3D-Based Solar System Learning Media Design to Improve Students’ Conceptual Understanding in IPAS Learning - Hadi Pranata; Muhammad Ikrom Karyodiputro (Journal of Educational Sciences, 2026)
This study aimed to examine the effectiveness of concrete 3D-based solar system learning media in improving elementary students’ conceptual understanding in Natural and Social Sciences (IPAS) learning. The novelty of this study lies in using a simple physical 3D solar system model, while previous studies mostly focused on digital media or augmented reality. This study was conducted at SDN Tenggarang 1 using a quantitative approach with a quasi-experimental method and a non-equivalent control group design. The sample consisted of 50 sixth-grade students, divided into an experimental class and a control class, each consisting of 25 students. Data were collected through conceptual understanding tests before and after learning. The data were analyzed using descriptive statistics, normality test, homogeneity test, paired sample t-test, independent sample t-test, and N-Gain analysis. The results showed that the experimental class mean score increased from 59.96 to 83.40, while the control class increased from 61.52 to 74.44. The independent sample t-test showed a significant difference between both classes, with a significance value of 0.000 < 0.05. The experimental class N-Gain reached 57.89%, categorized as moderately effective. Therefore, this media can be a practical alternative for elementary teachers, especially in schools with limited digital facilities.